1995
DOI: 10.1007/bf02143798
|View full text |Cite
|
Sign up to set email alerts
|

A molecular approach to galactosemia

Abstract: Classical galactosemia (G/G) is caused by the lack of galactose-1-phosphate uridyltransferase (GALT) activity. A more common clinical variant, Duarte/Classical (D/G) produces partial enzymatic impairment. Although neonatal death due to G/G galactosemia has been largely eliminated by population-based screening and intervention, long-term outcome in some is associated with impaired growth, ovarian failure, dyspraxic speech and neurologic deficits. At least 32 variants in the nucleotide sequence of the GALT gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 19 publications
1
47
2
Order By: Relevance
“…Additionally it was shown that the side chain of Gln-168 provided important hydrogen bonds to both O2 and O5Ј of the nucleotide. 5 It should be noted that in the human enzyme, the mutation of this glutamine to an arginine is the predominant cause of galactosemia among the Caucasian population (42). This change to an arginine residue may result in overstabilization of the enzyme intermediate, thereby compromising its subsequent reaction with galactose 1-phosphate.…”
Section: Minireview: Enzymes Of the Leloir Pathway 43886mentioning
confidence: 99%
“…Additionally it was shown that the side chain of Gln-168 provided important hydrogen bonds to both O2 and O5Ј of the nucleotide. 5 It should be noted that in the human enzyme, the mutation of this glutamine to an arginine is the predominant cause of galactosemia among the Caucasian population (42). This change to an arginine residue may result in overstabilization of the enzyme intermediate, thereby compromising its subsequent reaction with galactose 1-phosphate.…”
Section: Minireview: Enzymes Of the Leloir Pathway 43886mentioning
confidence: 99%
“…5). Finally, although R201H, L139P, E291K, and Y323D have all been identified in samples derived from patients with galac- tosemia, no data have been reported assigning specific GALT activity levels to these substitutions (9,44).…”
Section: Allelementioning
confidence: 99%
“…
A galactose breath test that quantitates [1][2][3][4][5][6][7][8][9][10][11][12][13] C]galactose conversion to 13 CO 2 provides information on the whole body galactose oxidative capacity. As there is little information on the relationship between whole body oxidation and the genotype in patients with galactosemia, we measured the 13 CO 2 excretion for 2 h after administration of [1-13 C]galactose in 37 patients (3-48 y old) with galactose-1-phosphate uridyltransferase (GALT) deficiency and 20 control subjects (3-37 y old).
…”
mentioning
confidence: 99%